THEOLOGICAL MODERATION IN THE ISLAMIC BOARDING SCHOOL (PESANTREN): PHENOMENOLOGICAL PROPHETIC SOCIAL STUDY IN PESANTREN IN EAST JAVA - Bosra, Mustari; Umiarso, Umiarso (AKADEMIKA: Jurnal Pemikiran Islam, 2020)
This article examines the construction of the religious moderation in pesantren which emphasizes the values framework that underlies it. Therefore, this research focused on the basic framework of theological normative values of the religious moderation in Islamic boarding schools (pesantren) in East Java. Based on this focus, this research emphasized a qualitative approach with a phenomenological type. The findings of this research review that the religious moderation built by the pesantren is based on divine awareness. Reasonably that their attitudes and actions continue to represent religious-spiritual values. Therefore, every dimension of their life is inseparable from Qur'anic ethics, including religious views, attitudes and actions. This is what the researcher termed aas theological moderation. The implication is not only to dynamize religious life in a society with various movements and beliefs but also to empower rationality (reason) in the pesantren, so that the educational system in the pesantren is also influenced by this religious moderation. Keywords: Islamic Education, Moderation, and Phenomenology